2022
DOI: 10.3389/fendo.2022.1052736
|View full text |Cite
|
Sign up to set email alerts
|

Association between metabolic scores for visceral fat and chronic kidney disease: A cross-sectional study

Abstract: IntroductionCentral obesity is closely linked to the risk of chronic kidney disease (CKD). This study aimed to evaluate the association between the novel central obesity index- metabolic score for visceral fat (METS-VF) and the risk of CKD in a Chinese population, and to compare its ability to predict CKD with other central obesity indices including waist circumference (WC), waist-to-height ratio (WHtR), lipid accumulation product (LAP), visceral adiposity index (VAI), a body shape index (ABSI), body roundness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…This study offers a thorough examination of the correlation between METS-VF and the potential for kidney stone formation, an area that has seen relatively little prior investigation. This research is groundbreaking in that it marks the first investigation of the association between METS-VF and kidney stone development ( 24 ). This study provides crucial information on the possible link between the two conditions, as well as the potential consequences for diagnosing and treating kidney stones.…”
Section: Discussionmentioning
confidence: 99%
“…This study offers a thorough examination of the correlation between METS-VF and the potential for kidney stone formation, an area that has seen relatively little prior investigation. This research is groundbreaking in that it marks the first investigation of the association between METS-VF and kidney stone development ( 24 ). This study provides crucial information on the possible link between the two conditions, as well as the potential consequences for diagnosing and treating kidney stones.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being a relatively new indicator that was first proposed in 2020, the METS-VF offers outstanding assessment capabilities across a wide range of disorders. In their study, Yu et al discovered that the METS-VF had a robust predictive capacity for chronic kidney disease (CKD) when in comparison to alternative evaluation markers of central adiposity [ 43 ]. Additionally, in comparison to other evaluation indicators of obesity, METS-VF demonstrates reliability and applicability as a predictor of hypertension and diabetes within the Chinese population [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that METS-VF had the strongest correlation with increased VAT in subjects in the validation cohort and had better predictive performance for increased VAT compared to BMI, VAI, LAP, WC and WHtR. Given the high accuracy and computational simplicity of METS-VF in predicting visceral obesity, more researchers have explored and confirmed its superior value in assessing and predicting the risk of visceral obesity-related diseases such as hyperuricemia, diabetes, CKD, and hypertension compared to other VAT surrogate indicators ( 19 23 ). However, to date, the relationship between METS-VF and NAFLD has not been reported.…”
Section: Discussionmentioning
confidence: 99%